Are classroom thermal conditions, lighting, and acoustics related to teacher health symptoms?. (23rd January 2020) - Lin, Shao; Lipton, Emily; Lu, Yi; Kielb, Christine
Abstract: Over half of schools surveyed in the United States reported one environmental problem affecting Indoor Air Quality. This study investigated environmental concerns in schools, teacher‐reported symptoms, and performance in relation to thermal environment, lighting, and noise conditions in New York State classrooms. This cross‐sectional study consisted of telephone surveys among teachers from 428 NYS public schools. Survey contents included teacher demographics, employment characteristics, and environmental factors. Unconditional logistic regression analyses were used to estimate odds ratios (OR) of health symptoms for classroom conditions including thermal environment, lighting, and acoustics. Although too dry, too hot, or cold were major thermal concerns, 78% of the teachers reported that they cannot control temperature through thermostat. Over 50% of NYS teachers reported almost all health symptoms worsening during workdays. We found the top five most common health symptoms reported by NYS teachers are all allergy‐related symptoms. Additionally, all extreme thermal factors were significantly associated with work‐related symptoms in teachers. "Too dry" had the highest risk for allergic symptoms (OR: 2.49, 95% CI: 2.01‐3.10), and then followed by any noise (OR: 2.46, 95% CI: 1.80‐3.36) associated with voice‐related health, and "lighting too dim" (OR: 2.38, 95% CI: 1.77‐3.19). Future studies are needed to confirm these findings.